Transparency and accountability in bribery prevention in village fund governance based on citizenship behavior - Arianto, Bambang; Oktaviani, Tita (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This research aims to elaborate on the strategy of transparency and accountability for the prevention of bribery in the management of village funds based on citizenship behavior.Design/Methodology/Approach: This research uses an ethnographic approach with in-depth interview techniques and participatory observation of several village governments in the Serang Banten Regency.Research findings: The results of the research found that strengthening transparency and accountability through digitization channels is one of the effective strategies for preventing bribery in managing village funds. This research also found that strengthening cultural values of cattle breeding and local wisdom can contribute to building awareness for the prevention of bribery practices in managing village funds.Theoretical contribution/ Originality: This research provides a scientific contribution to the prevention of fraudulent practices with the cultural approach of a region.Practitioner/Policy implication: This research can be a reference for various prevention practices for bribery in village fund management.Research limitation/Implication: This research is limited to Serang Banten Regency, which has a different community culture.